ANALISIS TOTAL PRODUCTIVE MAINTENANCE (TPM) PADA MESIN STRIP MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) PT XYZ - Ihsan, Tiaradia (LPPM Universitas Bina Bangsa, 2024)
PT XYZ is a company engaged in the pharmaceutical sector that supplies medicines in Indonesia. In the packaging of medicinal products, there are two types of packaging. Among them are primary packaging and secondary packaging. Chuan Yung Stripping Machine is one of the strip machines in the primary packaging production stage of drugs used by PT XYZ. Problems regarding the existence of defective products caused by the Chuan Yung Stripping machine resulted in several products that were defective either damaged, pinched, and there was too much dust on the machine. This occurs due to human error or errors that occur on the Chuan Yung Stripping machine. The method used in this research is to use Overall Equipment Effectiveness (OEE) by determining the availability rate, performance rate, and quality rate to analyze Total Productive Maintenance (TPM). The OEE value in January 2023 - December 2023 is 75%. This percentage is very far compared to the global standard of 85% due to the absence of OEE values that reach or exceed 85%. This happens due to high machine downtime. So the company must make improvements in order to improve product quality, work effectiveness and machines as well as in reducing the presence of defective products